(untitled) (Damascus University Journal for engineering sciences, 2025)
This article presents the results of a numerical simulation of arc antenna arrays composed of Yagi radiators. The governing determinants of the mutual effect between the radiators on the radiation pattern, the directivity of the array and the input impedance of the radiators were studied when using different amplitude and phase distributions to induce the radiators. In the analysis, the method of integrated equations was used.